Restoration of an Upper Anterior Tooth in an Adolescent with Autism Spectrum Disorder-A Student Case Report - Max Diekamp; Leonie Jenter; Andreas G. Schulte; Oliver Fricke; Peter Schmidt (MDPI AG, 2020)
Background: Patients with autism spectrum disorder (ASD) or other mental or physical limitations experience an imbalance in the frequency of dental treatment as compared with the general patient population, in part, due to inadequate pre-graduate training of future dentists. Case presentation: This case report describes a successful anterior tooth restoration, in awake state, in a 15-year-old boy with early childhood autism. The procedure was carried out independently by students of dentistry within the scope of their integrated clinical training semesters. Desensitization sessions were used as a preparatory measure and elements of behavioral facilitation (tell-show-feel-feel-do) were applied during the treatment. Conclusions: To avoid discrimination of this group of patients in the provision and quality of dental care, a structured approach to the transfer of theoretical and practical knowledge in the field of special care dentistry is indispensable. To this end, treatment strategies for special care patients should be taught to pre-graduate dental students as a fundamental part of their university curriculum.